Caracterização de resistência de genótipos de soja a Bemisia tabaci biótipo B (hemiptera: aleyrodidae) - Cruz, Patrícia Leite [UNESP] (2015)
Soybean, Glycine max (L.) Merrill, is one of the most important crops in Brazil with high productivity and expressive participation in exports. This leguminous is an important nutritional source for human and their derivatives may be used in animal feed or in the production of renewable energy as biodiesel. Although it has high production potential, the pest attack such as silverleaf whitefly, Bemisia tabaci (Gennadius) biotype B (Hemiptera: Aleyrodidae), undertakes a significant amount of the volume produced. This insect has become pest of economic importance to the soybean crop due to the increasing infestations and difficulties of management. The control of this hemipteran is made mainly through applications of synthetic insecticides, which are often overly utilized, having an impact on human and the environmental health. This situation encourages the study of less aggressive and more efficient alternatives, suitable to the integrated pest management (IPM). In this sense, the use of resistant genotype is considered a valuable tool, which can reduce the population of pests below the economic injury level without socio-environmental damage. In this work, 15 soybean genotypes were evaluated under attack of B. tabaci biotype B to characterize possible types of resistance (antixenosis, antibiosis and tolerance) against this insect. Initially, antixenosis assays were performed (free and no choice). The raise of the colonization of this insect confined to the genotypes and the characteristics of trichomes were also evaluated. In addition, biological performance tests were conducted to characterize the occurrence of antibiosis. In the last step, tolerance tests were conducted ...